EP.TH.174The FLIP Study – Fluid Resuscitation in Pancreatitis. (28th October 2021) - McGovern, Julia; Moir, John; Tingle, Sam; Hawthornwaite, Emma; Robinson, Stuart; ,
Abstract: Acute pancreatitis is a common condition encountered in emergency general surgical presentations. The severity of this condition can range from mild to severe and potentially life threatening in up to 20% of cases. Intravenous fluids are the cornerstone of management however there is very little guidance and poor quality evidence regarding optimal intravenous fluid administration. Aim to establish current clinical practice regarding the rate of intravenous fluid administration in acute pancreatitis and the effect this has on patient morbidity and mortality. A prospective multi-centre audit of patients presenting with acute pancreatitis in the North East of England (Sixty days recruitment with 30-day follow-up, November 2020 – February 2021). Patients aged 18 years or above with acute pancreatitis will be included. Data will be collected on intravenous fluid administration within 72 hours of admission. The primary outcome measure will be admission to HDU/ITU with secondary end-points including 30-day mortality, length of stay, radiological evidence of necrosis, and evidence of organ failure. Data collection has commenced across nine sites with over 150 patients recruited to date. The results of this study will be prepared in accordance with guidelines set by the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) statement for observational studies. Data will be analysed using SPSS. Statistical significance will be defined as a p value of ≤ 0.05. Data collection will be completed in February 2021. Pending the results of phase one, an RCT will be designed to determine the optimal rate of intravenous fluids for improved patient outcomes.